COMPREHENSIVE REVIEW OF HEALTH INFORMATICS TECHNICIAN CERTIFICATION EXAMINATIONS IN ASSESSING CONTENT VALIDITY, RELIABILITY, AND PREDICTIVE UTILITY FOR JOB PERFORMANCE - MUJIB SALEH DAFER ALALHARETH, AWADH AHMED ALI ALYAMI, MESFER ALI ALYAMI , NASSER SALEH M ALYAMI, MOHAMMED ALIMIHAMMED ALMAHARI, ZAYED MOHAMMAD ALI ALMUSHREF, FATHIYYAH AMER MOHAMMED ALSHAHRANI, WARDAH SAEED M ALYAQOOB (Chelonian Research Foundation, 2022)
Achieving a health informatics technician certification test remains an important indicator of performance level for professionals looking to prove their qualifications. The primary focus of this in-depth assessment is to determine the content validity, reliability, and productive potential of the examinations in terms of their usability as a predictor of job performance. This paper first conducts a comprehensive literature review and methodological analysis of current certification tests that address the integrity of these examinations in assessing the knowledge and skills of health information technicians. The results highlight the lack of scaled-down content validity and reliability among the various evaluations, which affects their ability to predict real-life on-the-job performances. Instructions to the health informatics technician examination developers about how to make the quality and effectiveness of the examination more rigorous are recommended. Keywords: health informatics, technician certification examinations, relevance of the training program, reliability, and predictive utility